E-MARKETING ROLE IN MEDIATING EFFECT OF ORGANIZATIONAL SUPPORT , TECHNOLOGY COMPETENCE, EXTERNAL ENVIRONMENT OF BUSINESS PERFORMANCE ON SMALL & MEDIUM ENTERPRISES (SMEs) IN KENDARI CITY - Indri Hapsari (Universitas Muhammadiyah Kendari, 2019)
Business through the Internet provides a great opportunity and a marketing strategy that is becoming a phenomenon is an e-marketing is a very fast development to achieve the service to consumers but has a number of complex challenges that need to support organizational, technological competence, the external environment will affect the performance of the business Small and Medium Enterprises in Kendari. The development and growth of e-marketing influence on the business have seen and felt by the public as well as principals of. The purpose of this study to analyze the role of e-marketing in mediating effect of organizational support, technology competence, the external environment of the Small and Medium Enterprise business performance in Kendari. This research was conducted on the perpetrators of Small and Medium Enterprises in Kendari many as 45 respondents using the nonprobability method of sampling through purposive sampling technique. Data were collected by questionnaires. The analysis technique used is Partial Least Square (PLS). Based on the analysis found Organizational Support direct effect on e-marketing. Furthermore, e-marketing directly affects the business performance of Small and Medium Enterprises (SMEs) in Kendari. The results of this study also prove that there is significant Organizational Support indirectly through e-marketing to business performance Small and Medium Enterprises (SMEs) in Kendari. While Technology Competence and External Environment show that there is no influence either directly or indirectly through e-marketing as a mediation on the Performance of Small and Medium Business in the City of Kendari.